Multiple Job-Holding in Indonesia: Do Years of Schooling Matter? - I Gede Putu Dharma Yusa; Aziz Wahyu Suprayitno; Faiz Abdullah Wafi (The Journal of Indonesia Sustainable Development Planning, 2025)
This study examines the impact of educational attainment, measured by individual years of schooling, on multiple job-holding in Indonesia. Utilizing data from the 2022 National Socio-Economic Survey (Susenas) for individuals aged fifteen and older, it examines both the decision to engage in multiple job-holding and the additional working hours outside the main job. To address potential sample selection bias, Tobit II (Two-Step Heckman) regression models are employed, with comparisons across models without controls, with controls, and with both controls and bias correction. The results show that over a quarter of employed individuals–approximately 27 percent–engage in multiple job-holding, contributing an average of more than four additional hours per week. Results from the Tobit II model suggest that higher levels of schooling are associated with a lower likelihood of multiple job-holding and fewer additional working hours. Multiple job-holding is found to be prevalent across all sectors, particularly in agriculture and informal employment, and is shaped by factors such as gender, working hours, land ownership, and urban-rural status. While education generally reduces multiple job-holding, its effect on additional hours varies across groups. The study recommends expanding educational access, enhancing protections and training for informal workers, and promoting rural and agricultural development to reduce necessity-based multiple job-holding and support more sustainable livelihoods.